Manajemen Usaha Sebagai Determinan Produktivitas Ayam Broiler dalam Sistem Kemitraan di Kecamatan Salahutu Kabupaten Maluku Tengah - Jomima Martha Tatipikalawan (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2026)
Broiler productivity within partnership farming systems in Salahutu District shows considerable variation, indicating the crucial role of farm-level management quality. This study aims to measure productivity levels and analyze the influence of managerial practices on broiler performance. The theoretical framework refers to livestock business management concepts emphasizing planning, labor organization, supervision, and control as key determinants of production outcomes. A survey of 11 respondent was conducted and analyzed using descriptive statistics and multiple linear regression. The results show an average mortality rate of 10.47% and a final body weight of 2.61±0.32 kg. Partially, business planning, labor management, and production supervision significantly affect productivity, whereas cost control and record-keeping do not. These findings highlight that broiler productivity is primarily driven by the quality of daily technical management within the partnership scheme